Quality of Life among Patient Affected with Hypertension in Kaushallya Memorial Hospital, Kohalpur, Banke - Acharya, Sabita (Academia Research Journal, 2024)
Hypertension is defined as the force exerted by circulating blood against the walls of the arteries, the major blood vessels in the body. Quality of life (QoL) is the subjectively determined personal satisfaction with daily life, as influenced by the individual’s evaluation of his/her physical, psychological, social, and spiritual wellbeing. The objective of this research was to assess quality of life among patient affected with hypertension in Kaushallya Memorial Hospital, Kohalpur, Banke. A descriptive cross-sectional research design was selected for the study and non-probability purposive sampling technique was used to select 60 hypertensive patients. Standarized questionnaire tool was used to collect data. The collected data were analyzed by using descriptive and inferential (ANOVA) statistic through SPSS version 21. The result of the study revealed that majority of the respondents 42(70.0%) had fair quality of life whereas quarter of the respondents 15(25.05) had poor quality of life and least of the respondents 3(5.0%) had good quality of life. The study shows that a higher Mental Health Scale domain score i.e.18.31 2.64. Role Emotional Scale domain has lowest score 5.05 1.87. It is concluded that general health domain, role physical domain, PFS, role emotional scale, SFS domain and vitality scale domain and role emotional domain of hypertension patient were affected.